Gaya Desain Interior Ruang Ibadah Karya Y.B. Mangunwijaya di Jawa Tengah - Laksmi Kusuma Wardani, Karen Sabrina Asiku (Intra, 2014)
Y.B. Mangunwijaya is known from his architectural and interior designed with emphasis in wastu citra, a design that fulfill the function of the building also the beauty which is created with the truth. Among of his works, the dominant of his design are the worship spaces. Santa Perawan Maria di Fatima church; interior relief in Panti Semedi chapel; Santa Maria Assumpta church; Angin Mammiri seminary; Santo Albertus Magnus Jetis church and chapel are chosen as the sample. This study used qualitative methods. All data were found with literature studies and interviews. The function of this study are to know the concept background and the application of Y.B. Mangunwijayaâs concept in this worship space. The results of this study indicate that the interior design style of worship space that Y.B. Mangunwijayaâs design relate with the value of Vatican IIâs, churches that open to the world. Also Y.B. Mangunwijaya uses diaspora church concept or churches that relate with Java cultural value, which is a new idea results from the mix between Y.B. Mangunwijayaâs background as an architect with an emphasis on wastu citra, wastu widya, and the values of the Christianity as well as Y.B. Mangunwijayaâs understanding of the traditional architectural style Java that is harmony with the natural environment. With this, Christianity value becomes harmony with the culture surround it.